Use of a 3D Floating Sphere Culture System to Maintain the Neural Crest-Related Properties of Human Dental Pulp Stem Cells - Pisciotta, Alessandra; Bertoni, Laura; Riccio, Massimo; Mapelli, Jonathan; Bigiani, Albertino; La Noce, Marcella; Orciani, Monia; de Pol, Anto; Carnevale, Gianluca (Frontiers in Physiology, 2018)
Human dental pulp is considered an interesting source of adult stem cells, due to the low-invasive isolation procedures, high content of stem cells and its peculiar embryological origin from neural crest. Based on our previous findings, a dental pulp stem cells sub-population, enriched for the expression of STRO-1, c-Kit and CD34, showed a higher neural commitment. However, their biological properties were compromised when cells were cultured in adherent standard conditions. The aim of this study was to evaluate the ability of three dimensional floating spheres to preserve embryological and biological properties of this sub-population. In addition, the expression of the inwardly rectifying potassium channel Kir4.1, Fas and FasL was investigated in 3D-sphere derived hDPSCs. Our data showed that 3D sphere-derived hDPSCs maintained their fibroblast-like morphology, preserved stemness markers expression and proliferative capability. The expression of neural crest markers and Kir4.1 was observed in undifferentiated hDPSCs, furthermore this culture system also preserved hDPSCs differentiation potential. The expression of Fas and FasL was observed in undifferentiated hDPSCs derived from sphere culture and, noteworthy, FasL was maintained even after the neurogenic commitment was reached, with a significantly higher expression compared to osteogenic and myogenic commitments. These data demonstrate that 3D sphere culture provides a favorable micro-environment for neural crest-derived hDPSCs to preserve their biological properties.